Segmental Arterial Mediolysis a Norepinephrine Induced Multi-guised Vasospastic Arteriopathy: Pathogenesis, Pathology and Clinical Presentations - Richard E. Slavin (Research Developments in Medicine and Medical Science Vol. 9, 2023)
Definition: Segmental arterial mediolysis (SAM) is a rare vasospastic, multiguised arteriopathy that affects the muscle arteries innervated by the peripheral sympathetic nervous system. It typically manifests in elderly people as catastrophic abdominal and retroperitoneal haemorrhages. Pathogenesis: SAM is initiated by the coupling of norepinephrine to plastically derived hyper dense foci of alpha-1 adrenergic receptors on the sarcolemma of arterial muscle. This ligand is created by stimuli signaled by iatrogenic sympathomimetic agonists, some Beta-2 agonists, or an excessive release of adrenal catecholamines. Coupling of this ligand with cytoplasmic heterotrimeric Gq protein excessively signals a cascade of biochemical events generating the two principal lesions of injurious phase SAM. Pathology: These are the shearing of the outer media from the adventitia and an overload of cytoplasmic calcium ions toxic to mitochondria causing mediolysis and/or apoptosis. The transmedial loss of the medial muscle causes gap-aneurysms, which burst and cause the enormous haemorrhages. The rapid development of a norepinephrine-directed reparative response either heals angiographic injury lesions or generates a body of vascular illnesses, the new guises of SAM, with ischemic clinical profiles. These present in the epicardial, vertebral, intestinal, and retroperitoneal arteries, often in younger females as fibromuscular dysplasia, dissecting hematomas, and persistent aneurysms. Norepinephrine can cross talk with serotonin and histamine to create SAM lesions and endothelin-1 in a field effect that generates venous fibromuscular dysplasia. Norepinephrine participates in the collateral development of mesangial hyperplasia with focal segmental glomerulosclerosis and myocardial mediolysis and apoptosis in subjects with markedly elevated heart rates. Conclusion: Norepinephrine coupling with plastically elevated alpha-1 adrenoceptor or other pressor agents generates SAM, a histologically recognizable vasospastic arteriopathy, that with repair is transformed into several different standardized arterial diseases that alter SAM’s clinical profile from a hemorrhagic to an ischemic disease.